Fixed point theorem between cone metric space and quasi-cone metric space - Al-Yaari, A. (Institute of Advanced Engineering and Science, 2022)
This study involves new notions of continuity of mapping between quasi-cone metrics spaces (QCMSs), cone metric spaces (CMSs), and vice versa. The relation between all notions of continuity were thoroughly studied and supported with the help of examples. In addition, these new continuities were compared with various types of continuities of mapping between two QCMSs. The continuity types are -continuous, -continuous, -continuous, and -continuous. The results demonstrated that the new notions of continuity could be generalized to the continuity of mapping between two QCMSs. It also showed a fixed point for this continuity map between a complete Hausdorff CMS and QCMS. Overall, this study supports recent research results. Â© 2022 Institute of Advanced Engineering and Science. All rights reserved.